Pengaruh Pengeluaran Belanja Daerah Terhadap Indeks Pembangunan Manusia Pada Kabupaten Padang Pariaman - Yuharmaen, Hendra; Ernawati, Ernawati (Universitas Sumatera Barat, 2019)
The purpose of this study was to see the effect of regional spending in the fields of education, health, and infrastructure on the Human Development Index (IPM) of Padang Pariaman Regency for the period 2015-2019. The population used in this study were all 17 Districts in Padang Pariaman Regency from 2015 to 2019. The sample used was 17 Districts in Padang Pariaman Regency from 2015 to 2019 with purposive sampling technique. The type of data in this study using secondary data is data that is already available for the agencies involved. The model analysis in this study and the panel data regression program used to process the classic assumption test using EVIEWS 10. The results of the analysis show that the education sector regional spending (X1) affects the Human Development Index (Y) in Padang Pariaman Regency. Regional health expenditure (X2) does not affect the Human Development Index (Y) in Padang Pariaman Regency. Regional spending on infrastructure (X3) affects the Human Development Index (Y) in Padang Pariaman Regency.